Stress Level And Hemodialysis Duration Of Patients With Chronic Kidney Failure Undergoing Hemodialysis - Soeli, Yuniar M.; Amu, Ivan Virnanda; Sune, Ziah Anisa (Universitas Aisyah Pringsewu, 2021)
Kidney failure is a chronic and irreversible impaired kidney function. End-stage kidney disease requires therapy, namely hemodialysis using a dialysis machine, in which the process takes a long time. Such a duration of therapy can lead to anxiety and stress to the patient. The study aims to determine the relationship between stress level and hemodialysis duration among patients with chronic kidney failure who underwent hemodialysis at Toto Kabila Regional Public Hospital.This research employed a cross-sectional method involving patients suffering from kidney failure and undergoing hemodialysis as the population. Further, the sample consisted of 29 respondents with a total sampling technique. The results showed that one respondent (3.4%) experienced normal stress, eight respondents (27.6%) had mild stress, 15 respondents (51.7%) got moderate stress, and five respondents (17.2%) experienced severe stress. In addition, two respondents underwent hemodialysis therapy for less than 6 months, and 27 respondents (93.1%) were under the therapy for more than 6 months.All in all, stress level relates to hemodialysis therapy of patients with chronic kidney failure who undergo hemodialysis in the aforementioned hospital. The p-value was 0.021 less than 0.05, indicating that Ha is accepted. It is suggested that people think positively and composedly during circumstances to live a better life.